Distribution of paracalanidae species (Copepoda, Crustacea) in the continental shelf off Sergipe and Alagoas States, Northeast Brazil (Brazilian Journal of Oceanography, 2006)
The spatial and seasonal distribution of the Paracalanidae species were studied in eighteen stations in the continental shelf off Sergipe and Alagoas States, northeast Brazil, in December, 2001 and 2003, and in June, 2002 and 2003. The Paracalanidae family was constituted by coastal and shelf species such as Parvocalanus crassirostris, Paracalanus quasimodo, P. indicus and P. aculeatus and oceanic species, Calocalanus pavo and Acrocalanus longicornis. Density values were higher in stations located at 10 m isobath with respect to those located at 20 and 30 m depths. Paracalanidae abundance presented differences between seasons with values higher in June (2002, 2003) than in December (2001, 2002). All species were more abundant in the rainy season except Parvocalanus crassirostris. Paracalanus quasimodo was the dominant species with average densities of 949, 740 and 41 ind.m-3 in December months and 4231, 2389 and 1185 ind.m-3 in June months, at stations with local depths of 10, 20 and 30 m, respectively. Canonical correspondence analysis showed that salinity and temperature were the environmental variables that presented significant correlation with the distribution of Paracalanidae species, probably because these variables are influenced by the estuarine waters and by the dynamic of oceanic water masses in the continental shelf.